Diseases of poultry - Swayne, David E. (Hoboken, NJ : Wiley-Blackwell, 2020)
"The most complete and definitive reference to all aspects of poultry diseases, Diseases of Poultry, Fourteenth Edition has been fully revised and updated to offer a comprehensive survey of current knowledge. Updates the definitive reference of poultry health and disease Provides more clinically relevant information on management of specific diseases, contributed by clinical poultry veterinarians Offers information on disease control in organic and antibiotic-free production Presents more concise, streamlined chapters for ease of use Incorporates advances in the field, from new diagnostic tools and information to changes brought about by the increasing globalization and the re-emergence of zoonotic pathogens"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Poultry Diseases; Aves de corral -- Enfermedades